2006
DOI: 10.1097/01.qai.0000225729.79610.b7
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Decline and Incidence of Opportunistic Infections in Cape Town, South Africa

Abstract: : CD4 cell count declines were dependent on CD4 strata and can inform timing of clinic visits and treatment initiation in South Africa. Incidence rates of OIs suggest that targeted OI prophylaxis could prevent substantial HIV-related morbidity in South Africa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
147
2
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 28 publications
15
147
2
2
Order By: Relevance
“…Several studies have pointed out that the use of probiotics can significantly improve the wellbeing of individuals infected with HIV/AIDS (Anukam, 2007). For example, studies conducted in Africa have estimated the average annual increase in CD4 count of 90cells/mL with ARV treatment (Lawn et al, 2006) and an average decline of 20 to 50 cells/mL/year without ARV treatment (Holmes et al, 2006;Urassa et al, 2004). In the Tanzanian study, (Irvine et al, 2010), a similar rate of increase was observed of 99 cells/mL with ARV treatment (0.27 cells/mL/d), whereas no significant decrease was observed without ARV treatment.…”
Section: Can the Use Of Probiotics Make An Impact In Africa?supporting
confidence: 53%
“…Several studies have pointed out that the use of probiotics can significantly improve the wellbeing of individuals infected with HIV/AIDS (Anukam, 2007). For example, studies conducted in Africa have estimated the average annual increase in CD4 count of 90cells/mL with ARV treatment (Lawn et al, 2006) and an average decline of 20 to 50 cells/mL/year without ARV treatment (Holmes et al, 2006;Urassa et al, 2004). In the Tanzanian study, (Irvine et al, 2010), a similar rate of increase was observed of 99 cells/mL with ARV treatment (0.27 cells/mL/d), whereas no significant decrease was observed without ARV treatment.…”
Section: Can the Use Of Probiotics Make An Impact In Africa?supporting
confidence: 53%
“…We assumed that, compared to HIVnegative individuals, the incidence of TB would be 2, 4, 8, and 16 times higher among HIVpositive individuals with CD4+ counts >500, 350-500, 200-350, and <200, respectively [18][19][20][21]. Finally, we assumed HIV-specific mortality rates of 0.1/year for individuals with CD4+ counts higher than 200, and 0.35/year in individuals with CD4+ counts less than 200 [22].…”
Section: Hiv Prevalence Art Coverage and Hiv-tb Co-infectionmentioning
confidence: 99%
“…1, solid blue bars in panel C versus solid bar in panel D). Finally, we assumed effects of HIV on TB incidence in both mines and the labor-sending community as described above [18][19][20][21]. (Fig.…”
Section: Data and Model Calibrationmentioning
confidence: 99%
“…28 Patients in care received cotrimoxazole prophylaxis at CD4 <200/µL, 29 generally reducing OD risk.…”
Section: Natural Historymentioning
confidence: 99%